Exact estimates of solutions to the robin boundary value problem for linear elliptic non divergence second order equations in a neighborhood of the conical point - Borsuk, M.; Zawadzka, A. (Нелинейные граничные задачи, 2004)
We investigate the behavior of strong solutions to the Robin boundary value problem for linear elliptic non divergence second order equations in a neighborhood of the boundary conical point. We establish precise exponent of the solution decreasing rate.